Noragami. stray god 7 - Adachi, Toka (Kodansha Comics, 2015)
The fight with Bishamon is over and it's time for Yato to tie up some loose ends -- or cut ties with Hiyori, as he promised Tenjin. But a nameless god like Yato can't survive unliess he remains in someone's memory. How will he manage once he is removed from Hiyori's life?